The Soul of Susan Yellam - Vachell, Horace Annesley, 1861-1955 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Soul of Susan Yellam" by Horace Annesley Vachell is a novel written in the early 20th century. It explores the lives of residents in the village of Nether-Applewhite, particularly focusing on a mother, Susan Yellam, and her son, Alfred, as they navigate daily life, relationships, and the social expectations of their community. The story sets the stage for themes of love, tradition, and the subtle changes brought about by modernity. At the start of the novel, Susan Yellam is portrayed as a formidable figure in her village, devoted to her family, particularly her son, Alfred, who is a bachelor and carries on the family tradition as a carrier. The opening chapter introduces their routine Sunday at church when Susan notices a new parlourmaid, Fancy Broomfield, which prompts her to contemplate Alfred's single status and potential marriage. This sets off a series of reflections on societal norms, the dynamics of village life, and the possibilities of romance as Alfred begins to take an interest in Fancy. The complex interplay of characters and their social positions hints at the unfolding drama in the face of traditional values and emerging desires for change. (This is an automatically generated summary.)
Release date is 2011-06-14
E-text prepared by Juliet Sutherland, Carol Brown, and the Online Distributed Proofreading Team
Keywords: World War, 1914-1918 -- Fiction; Villages -- England -- Fiction; England -- Social life and customs -- 20th century -- Fiction